2018
DOI: 10.1136/bmjopen-2017-019076
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal body weight and sputum conversion in patients with tuberculosis, Southwest Ethiopia: a retrospective follow-up study

Abstract: ObjectivesTo describe the association between change in body weight and sputum smear conversion and to identify factors linked with body weight and sputum smear conversion in Jimma University Specialized Hospital, Southwest Ethiopia.DesignA retrospective follow-up study.SettingTeaching hospital in Southwest Ethiopia.ParticipantsA total of 450 patients with tuberculosis (TB) were included in the follow-up between 2011 and 2013.Main outcome measuresThe association between body weight and sputum conversion was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
3
2
0
Order By: Relevance
“…The odds of getting weight for patients who have no HIV/AIDS were 3.3 times as compared to HIV positives. This finding is in line with studies conducted in Jimma and Tanzania revealed HIV status has a significant association with weight gain [15,18]. This could be due to the effect of HIV/AIDS on immunity as well the effect of pill burden for drug [13], this could be due to awareness variations and special care given for HIV/AIDS patients in Addis Ababa.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The odds of getting weight for patients who have no HIV/AIDS were 3.3 times as compared to HIV positives. This finding is in line with studies conducted in Jimma and Tanzania revealed HIV status has a significant association with weight gain [15,18]. This could be due to the effect of HIV/AIDS on immunity as well the effect of pill burden for drug [13], this could be due to awareness variations and special care given for HIV/AIDS patients in Addis Ababa.…”
Section: Discussionsupporting
confidence: 90%
“…This could be due to the effect of HIV/AIDS on immunity as well the effect of pill burden for drug [13], this could be due to awareness variations and special care given for HIV/AIDS patients in Addis Ababa. The odds of weight gain for patients who have not any parasitic disease during treatment is 3 times as compared to those who were having parasitic disease, and the finding is in line with studies conducted in Jimma and Tanzania revealed patients who have not any intestinal parasite were getting weight as compared to their counterpart [15,18]. This could be due to the effect of intestinal parasites on nutrition as well the effect of pill burden for drug compliance.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The importance of increasing body weight in TB patients through proper nutrition to improve their physical health and treatment outcomes has been widely recognized [36][37][38][39]. This study confirms that patients who had a baseline weight of over 53kg or gained at least 3kg of body weight during treatment achieved successful outcomes, consistent with findings from Peru and Ethiopia [39,40].…”
Section: Discussionsupporting
confidence: 84%
“…Anaemia and weight loss are prognostic of delayed sputum conversion and mortality in TB disease and the association with CD4+ T-lymphocytopenia may be indicative of severe TB disease. [28][29][30][31] Therefore, CD4+ T-lymphocytopenia is likely to have prognostic importance even among HIVnegative TB patients. 32 In support of this, baseline levels of some subsets of CD4+ T-lymphocytes have been shown to predict TB culture conversion.…”
Section: Discussionmentioning
confidence: 99%